Диагностика конкурентоспособности промышленных предприятий - Алешин, Сергей Юрьевич (АНАЛИТИКА РОДИС, 2015)
В статье отмечается, что в текущих условиях хозяйствования проблема конкурентоспособности промышленных предприятий становится одной из ключевых. Анализ сущности понятия «конкурентоспособность» позволяет выделить ключевые его характеристики, внести необходимые уточнения. Среди существующих методов оценки уровня конкурентоспособности предприятий автор акцентирует внимание на интегральном методе, предлагается алгоритм расчета интегрального показателя конкурентоспособности предприятий с использованием мультипликативного подхода, формируется необходимая система частных индикаторов.

The article deals with the peculiarities of the diagnostics of the competitive capacity of industrial enterprises. The author of the article states that in the current economic conditions the problem of competitiveness of industrial enterprises has become one of the key issues. The analysis of the essence of the concept of "competitiveness" allows of determining its key features and giving a more precise definition. There are several methods that can be used for assessing the degree of the competitiveness of enterprises, but the author of the article pays special attention to the integral method. The article proposes an algorithm for calculating the integral index of the competitiveness of enterprises with the use of a multiplicative approach, as well as the necessary system of particular indicators. The proposed approach to the assessment of the competitive capacity of industrial enterprises, which is based on the system of certain indicators and the chosen integral method of calculation, allows of carrying out the comprehensive assessment of the competitive capacity of economic entities and creating the necessary conditions for making prompt managerial decisions about the enterprise development strategy, the formation of long-term competitive advantages, the latter often being formed on the basis of innovative activity.
Diagnostics of the competitive capacity of industrial enterprises
Keywords: управление предприятием; менеджмент; контроллинг; потенциал инновационный; метод интегральный; эффективность экономическая; рентабельность; ликвидность; стабильность финансовая; капитал; персонал; модель мультипликативная; решения управленческие; assessment; competition; competitive capacity; integral method